Corn‐like mSiO2@ZIF‐8 Composite Load with Curcumin for Target Cancer Drug‐Delivery System. Issue 47 (14th December 2022) - Chen, Menglan; Song, Fangxiang; Wu, Nian; Luo, Honghuan; Cai, Xiaoqin; Li, Yan
Abstract: To improve the drug loading rate of mesoporous silica (mSiO2 ), mSiO2 nanorods were synthesized by a modified sol‐gel method, then mSiO2 @ZIF‐8 nanoparticles were prepared by using mSiO2 nanorods as the matrix. The structure of mSiO2 and mSiO2 @ZIF‐8 were characterized. The results show that mSiO2 @ZIF‐8 nanoparticles are corn‐like, with a specific surface area of 116.81 m 2 g −1, pore volume of 0.31 cm 3 g −1, and pore size of 8.43 nm. Curcumin (CUR) was used as an anti‐tumor model drug in drug delivery experiments. The drug loading rate of mSiO2 @ZIF‐8 for CUR is 21.39 %. Before modification by Chitosan (CS) and folic acid (FA), the cumulative release rate of CUR is 30.27 % at pH 5.6 and 26.26 % at pH 7.4. After been target functionalized by CS and FA. At pH 5.6 and pH 7.4, the cumulative release rates are 34.21 % and 20.48 %, respectively, within 228 h after drug release in vitro. The results show that the drug delivery system has good pH responsiveness. Zero‐order, first‐order, Higuchi, Hixson Crowell, and Korsmeyer Peppas models were used to describe the release kinetics of mSiO2 @ZIF‐8@CUR. The Higuchi model provides the highest fit for the CUR release of mSiO2 @ZIF‐8@CUR. Abstract : In this paper, a corn‐like mSiO2 @ZIF‐8 nano drug delivery system was prepared to load CUR and the CS and FA were used to functionalizethe drug delivery system .The cumulative release rate of CUR under different pH conditions was been investigated. The results show the drug delivery system has good pH responsiveness.